The Influence of Health Education on the Dangers of Early Marriage with Adolescents' Knowledge Level at SMA Negeri 2 Gorontalo - Dinda Febriyani Ishak; Ita Sulistiani; Nur Fitriah Jumatrin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Early marriage is still a serious problem in Indonesia, including in Gorontalo Province, the impact of early marriage such as school dropouts, psychological problems, and reproductive health risks in adolescents. Prevention efforts that can be carried out include health education to increase adolescents' knowledge about the dangers of early marriage. The study aims to determine the influence of health education about the dangers of early marriage on the level of knowledge of adolescents at SMA Negeri 2 Gorontalo. The study used a quantitative method with a pre-experimental design in the form of a group with pre- and post-intervention measurements. The study population was 756 students in grades X and XI. The research sample amounted to 88 respondents with stratified random sampling techniques. Interventions are provided through face-to-face health education with leaflet and poster media. The collection used a knowledge questionnaire of 30 items. Data analysis was conducted using the Paired Sample T-Test. The results showed that before being given health education, the majority of respondents had a moderate level of knowledge of 60 respondents (68.2%) with an average score of 19.18. After being given health education, the majority of respondents had a high level of knowledge as many as 67 respondents (76.1%) with an average score of 24.65. The results of the Paired Sample T-Test showed a p-value = 0.000 (p < 0.05), so it can be concluded that there is an influence of health education about the dangers of early marriage on the level of knowledge of adolescents at SMA Negeri 2 Gorontalo. Health education has been proven to be effective in increasing adolescents' knowledge as a promotive and preventive effort in preventing early marriage.